Pengaruh Board Diversity Pada Nilai Perusahaan Dalam Perspektif Corporate Governance - Yogiswari, Ni Luh Putu Purna; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 26 No 3 (2019), 2019)
Board composition is one particular issue regarding corporate governance. This study aims to find empirical evidence regarding the effect of board diversity proxied by gender diversity, nationality diversity, educational background, and the proportion of outside directors on firm value. This research was conducted in basic industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange with an observation period of 3 years, those of from 2015-2017. The method of determining the sample uses a purposive sampling. The sample of this study amounted to 39 companies with a total of 117 samples. Based on the results of the analysis, it can be concluded that gender diversity and the proportion of outside directors have no effect on firm value while there is a positive effect between nationality diversity and educational background on firm value. Keywords: Board diversity, corporate governance, and firm value.